Iodine/tert‐Butyl Hydroperoxide‐Mediated Reaction of Indoles with Dimethylformamide/Dimethylacetamide to Synthesize Bis‐ and Tris(indolyl)methanes. Issue 1 (9th January 2017) - Deb, Mohit L.; Borpatra, Paran J.; Pegu, Choitanya Dev; Thakuria, Ranjit; Saikia, Prakash J.; Baruah, Pranjal K.
Abstract: Here we report a metal‐free iodine/ tert ‐butyl hydroperoxide mediated reaction of N‐substituted indoles with dimethylformamide (DMF) / dimethylacetamide (DMA). The reaction produces bis‐ and tris(indolyl)methanes (BIMs and TIMs), in which DMF/DMA provides the methylene (of BIMs) and methine carbons (of TIMs). We have established different optimized conditions for their synthesis. Iodine (10 mol %) with TBHP (in decane, 1.0 equivalent) in DMF/DMA at 130 °C is required for the BIMs synthesis, whereas iodine (20 mol %) with TBHP (in water, 3.0 equivalent) in DMF‐H2 O or DMA‐H2 O (9:1) is needed for the TIMs. This methodology could be used to synthesize a variety of BIMs and TIMs. We believe, this is the first report of their metal‐free synthesis through C−H functionalization using one carbon source. The use of inexpensive, metal‐free and environmentally benign catalyst made the method handy. Abstract : Indoles react with DMF or DMA in presence of I2 ‐TBHP to give bis‐ and tris(indolyl)methanes. In this reaction DMF and DMA act as carbon sources. Alkylideneindoleninium ion is the key intermediate for the synthesis of both the compounds.